The influence of the blade feather constructional inhomogeneity on the turbine cooling blades stress-strain state - Morhun, Serhii (Eastern-European Journal of Enterprise Technologies, 2018)
The problem of gas turbine engines inhomogeneous rotor blades stress-strain state has been studied. For this purpose, the new, more correct mathematical model, based on the special three-dimensional curvilinear finite elements has been used. Such elements have three modifications, applied for the blade feather and its transition zones correct modeling. The complex influence of vibration and heat loads on the blade feather has also been taken into consideration. The values of maximum dynamic stresses and their localization zones have also been found. The main concentrators of stresses are located in the transfer zones between the cooling channels and blade feather surfaces. The blade output edge is another zone of maximum dynamic stresses localization. It has also been found that the influence of the geometric parameters of cooling channels in the blade feather cavity on the value of maximum dynamic stresses is sharper than the influence of cooling holes on the blade output edge. By comparing the obtained calculated results with the experimental data, we can state the high adequacy and reliability of the developed mathematical model. All calculations and experimental procedures were held by equal boundary conditions. The results of the research can be used as a base for further studying of the whole rotor stress-strain state and processes of blades fatigue destruction.